INTRODUCING SEDIMENTOLOGY - JONES, STUART (DUNEDIN ACADEMIC PRESS, 2023)
Sedimentary rocks cover most of the Earth's surface, recording much of the Earth's history and fossil record. In this thoroughly revised and updated popular student introduction the author provides a comprehensive, illustrated overview of sedimentary rock types, structures and depositional environments.
Keywords: elektronické knihy; electronic books